2018
DOI: 10.1093/intqhc/mzy177
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant medication errors in hospitals and primary care: a cross-sectional study

Abstract: Anticoagulant medication errors occurred in 8.3% of all medication errors. Most error reports concerned the prescribing phase of the medication process. Leading cause was human factors. The publication of the guideline had no effect on the proportion of anticoagulant medication errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…anticoagulant-related medication errors occurred mainly in the prescribing phase and in about 56% of errors lowmolecular-weight heparins (LMWH) were involved [2,4]. Consistently, a similar descriptive study on the Danish patient safety database reported that the adverse medication incidents occurred mainly in the prescribing phase, and in about 80% of incidents the errors occurred at the time of sector changes (at the admission, at the discharge or ward changes) [5].…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…anticoagulant-related medication errors occurred mainly in the prescribing phase and in about 56% of errors lowmolecular-weight heparins (LMWH) were involved [2,4]. Consistently, a similar descriptive study on the Danish patient safety database reported that the adverse medication incidents occurred mainly in the prescribing phase, and in about 80% of incidents the errors occurred at the time of sector changes (at the admission, at the discharge or ward changes) [5].…”
mentioning
confidence: 68%
“…Despite similarities of different reports in showing the high frequency of AC-associated medication errors, there are discrepancies regarding involved AKs, the proportion of error types, and the time of medication process in which errors occur. It seems that the following parameters play a role in the above-mentioned discrepancies: time of study according to the first appearance of the newer AK agents, pharmaceutical market varieties among countries in which the studies have been done, and the difference in study population [2,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PPS has proven to be useful to evaluate MRPs as e.g. medication errors relating to anticoagulants, problems related to IT‐matters, or problems related to automatic dose dispensing 22–24 . A systematic evaluation of any MRP relevant to older people and (potentially) connected with the drug product design has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%